2014
DOI: 10.1186/1472-6750-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Improved production of recombinant human Fas ligand extracellular domain in Pichia pastoris: yield enhancement using disposable culture-bag and its application to site-specific chemical modifications

Abstract: BackgroundA useful heterologous production system is required to obtain sufficient amounts of recombinant therapeutic proteins, which are often necessary for chemical characterization and engineering studies on the development of molecules with improved properties. Human Fas ligand extracellular domain (hFasLECD) is an agonistic death ligand protein that has potential applications for medical purposes. Site-specific chemical modifications can provide a powerful means for the development of engineered proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The production of NFK3G1CG4-hFasLECD in a P. pastoris secretory expression system was conducted as described previously [19]. hFasRECD-Fc was produced in a baculovirus – Bombyx mori expression system and purified as described in the previous paper [36].…”
Section: Methodsmentioning
confidence: 99%
“…The production of NFK3G1CG4-hFasLECD in a P. pastoris secretory expression system was conducted as described previously [19]. hFasRECD-Fc was produced in a baculovirus – Bombyx mori expression system and purified as described in the previous paper [36].…”
Section: Methodsmentioning
confidence: 99%
“…1 ) as well as from the fairly hydrophilic property of the N-terminal FLAG tag plus aa 139-142 region (Asp–Tyr–Lys–Asp–Asp–Asp–Asp–Lys–Gly–Cys–Gly–Gly–Gly–Gly–Glu–Lys–Lys–Glu), the unpaired Cys was expected to locate not proximal to the binding interface, but exposed to the solvent in an aqueous solution of neutral pH. Although the pre-activation by a treatment with some reducing agents was necessary for an efficient conjugation because of the propensity to form a disulfide-bridge between two NFG1CG4-hFasLECD monomer subunits due to non-specific oxidation of the unpaired cysteine residue, it was demonstrated that selective activation of the conjugation site alone was possible by choosing the mild reducing condition using TCEP for the reaction in the previous study (Muraki 2014b ). Moreover, the resulting conjugates with several kinds of single or double maleimide group(s) containing compounds maintained the receptor binding activity, and also one conjugate was proved to exhibit significant cytotoxic activity against a cancer cell line after cross-linking by an anti-FLAG tag antibody (Muraki 2014b ).…”
Section: Resultsmentioning
confidence: 99%
“…hFasLECD containing single deletion mutation from 103 to 138 and double substitution mutations (N184Q and N250Q) [hFasLECD (139-281, N184Q, N250Q)] with an N-terminal FLAG-(GlyCysGlyGlyGlyGly) tag sequence (NFG1CG4-hFasLECD) and that with an N-terminal FLAG-(Gly) 5 tag sequence (NFG5-hFasLECD) were prepared as described (Muraki 2008 , 2014b ). FL-5Mal was obtained from Tokyo Chemical Ind.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations